Human development and the international development strategy for the 1990's / edited by Keith Griffin and John Knight - Keith Griffin (London, 1990)
The book makes a strong and convincing case for a renewed emphasis on human development both to foster economic growth and as an end in itself. Policies for human development enhance the 'capabilities' of people to be and to do things. This book brings together contributions by recognised experts on various aspects of human development - educational policy, health and nutrition, technological capabilities, and the harnessing of local resources - and builds on them to advocate a redirection of policies for the 1990s.
Keywords: Economic development